Acid and weakly acidic solutions impair mucosal integrity of distal exposed and proximal non-exposed human oesophagus. Issue 2 (1st November 2009) - Farré, Ricard; Fornari, Fernando; Blondeau, Kathleen; Vieth, Michael; De Vos, Rita; Bisschops, Raf; Mertens, Veerle; Pauwels, Ans; Tack, Jan; Sifrim, Daniel
Abstract : Background: Oesophageal mucosa dilated intercellular spaces (DIS) may be important for symptom perception in non-erosive reflux disease (NERD). Patients with NERD might have DIS even in the proximal oesophagus. We aimed to assess the effect of oesophageal perfusions with acid and weakly acidic solutions on 'exposed' and 'non-exposed' oesophageal mucosa and its relationship to symptoms in healthy subjects. Methods: 14 healthy volunteers underwent upper gastrointestinal endoscopy with biopsies at 3 and 13 cm proximal to the oesophagogastric junction (OGJ). In following sessions, subjects received 30 min perfusions with neutral, weakly acidic, acidic and acidic-bile acid solutions at 5 cm above the EGJ (separated 4 weeks). Biopsies were taken 20 min after perfusions. Electron microscopy was used to measure DIS. Subjects scored heartburn during perfusions using a visual analogue scale. Results: (1) Oesophageal perfusion with acid solutions, with or without bile acids, provoked DIS in the 'exposed' oesophageal mucosa; (2) oesophageal perfusion with weakly acidic solutions provoked identical changes to those observed after perfusion with acid solutions; (3) distal oesophageal perfusions not only provoked changes in the 'exposed' but also in the more proximal 'non-exposed' mucosa; and (4) in spite of the presence of perfusion-induced DIS, most healthy subjects did not perceive heartburn during the experiments. Conclusions: The human oesophageal mucosa is very sensitive to continuous exposure with acidic and weakly acidic solutions. In spite of the presence of intraluminal acid and DIS, healthy subjects did not experience heartburn, suggesting that NERD patients should have other critical factors underlying their symptoms.